ANALISIS KOEFISIEN KEBUTUHAN MATERIAL DAN TENAGA DENGAN METODE ANALISIS BURGERLIJKE OPENBARE WERKEN (BOW) DAN METODE ANALISIS SNI 2008 TERHADAP EFISIENSI ALUR PENGADAAN MATERIAL DI PROYEK (Studi Kasus : Bangunan Tenant-150, Project Awann Costa POJ, Semarang) - Octaviana, Luthfia Dea; Permata Suwandi, Putri Anggi; Rizani, Mohammad Debby (Universitas PGRI Semarang, 2024)
The development of construction planning, especially in the construction of building structures, calculates unit prices using a tool called Construction Cost Analysis (ABK), where until now the method often used by contractors and consultants is the BOW (Burgerlijke Openbare Werken) guideline. However, as time went by, it was realized that the BOW guidelines were only segmentally suitable for projects in the form of labor-intensive work that utilized conventional equipment and less professional workforce, which resulted in very expensive planning costs if this approach was still used purely. The 2008 Indonesian National Standard (SNI) analysis method is an update of the 1921 BOW (Burgerlijke Openbare Werken) analysis during the Dutch government, in other words, the SNI analysis is an updated BOW analysis. This SNI analysis was issued by the Center for Settlement Research and Development. The cost preparation system using SNI analysis is almost the same as the calculation system using BOW analysis. The basic principle of the SNI method is that a list of coefficients for materials and labor costs has been determined to analyze the price or costs required to make a unit price for building work. From these two coefficients we will get a calculation of the materials needed and a calculation of the wages of those doing the work. The comparative composition and arrangement of materials and labor for one job has been determined, which is then multiplied by the price of materials and wages prevailing in the market.